Polymeric Systems for Colon-specific Mesalazine Delivery in the Intestinal Bowel Diseases Management - Tavares Junior, Alberto Gomes [UNESP]; de Araújo, Jennifer Thayanne Cavalcante [UNESP]; Duarte, Jonatas Lobato [UNESP]; Silvestre, Amanda Letícia Polli [UNESP]; Di Filippo, Leonardo Delello [UNESP]; Chorilli, Marlus [UNESP] (Bentham Science Publishers, 2023)
The anti-inflammatory 5-aminosalicylic acid (5-ASA) is the main therapeutic option used to prevent and treat inflammatory bowel diseases. The upper intestinal tract performs rapid and almost complete absorption of this drug when administered orally, making local therapeutic levels of the molecule in the inflamed colonic mucosa difficult to achieve. Micro and nanoparticle systems are promising for 5-ASA incorporation because the reduced dimensions of these structures can improve the drug's pharmacodynamics and contribute to more efficient and localized therapy. Together, the association of these systems with polymers will allow the release of 5-ASA through specific targeting mechanisms to the colon, as demonstrated in the mesalazine modified-release dosage form. This review will summarize and discuss the challenges for the oral administration of 5-ASA and the different colon-specific delivery strategies using polymers.
Keywords: 5-ASA; colonic delivery; microparticles systems; modified-release dosage forms; nanoparticles systems; polymeric systems